Analisis Perilaku Organizational Citizen Ship Behavior ( OCB ) Karyawan di PT. Yangtze Optical Fibre Indonesia - Muhammad Candra Rosid; Uus MD Fadli (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Organizational Citizenship Behavior (OCB) is a concept that emphasizes individual extra-role behavior in organizations. OCB includes behaviors such as helping co-workers, taking on tasks that are not listed in the job description, and promoting a positive work atmosphere. The purpose of this research is to find out the behavior of each individual outside of their main duties in the organization or work that helps strengthen the organization. Includes behaviors such as helping colleagues, maintaining a clean and orderly work environment, and showing a high commitment to the organization. This study uses a qualitative descriptive approach. Research Locus at PT. YOFC, the informants were one shift leader and one chief operator selected by purposive sampling. Data was collected through in-depth interviews, field surveys and secondary data recording as needed.